PEMANFAATAN MINYAK SAWIT MERAH DALAM PEMBUATANBISKUIT KACANG KAYA BETA KAROTEN [Utilization of Red Palm Oil To Produce BetaCarotene-Rich Nuts Biscuit] - Robiyansyah, Robiyansyah; Zuidar, Ahmad Sapta; Hidayati, Sri (Jurnal Teknologi & Industri Hasil Pertanian, 2017)
The purpose of this research was to get formulation of red palm oil and cooking oil to produce nuts biscuits with the best organoleptic properties. The formula consisted of red palm oil and cooking oil mixture with 6 comparisons: (0:100), (20:80), (40:60), (60:40), (80:20) and (100:0). These formula were then used as basis to produce nuts biscuits. Observation was done on the organoleptic properties (aroma, texture, taste and color for all biscuits) for all samples, while proximates test (water, fat,protein,ash content) and betacarotene content were done only for the best formulation. The data were descriptively analyzed and presented in tables and graphs. The best organoleptic properties of these betacarotene rich nuts biscuits was formulation of 20:80. This biscuits had water content 1,42%, ash content 1,21%, fat content 32,60%, protein content 12,59%, and the total of beta carotene 347,15 ppm, with the less normal for aroma (4,55), less crunchy for the texture (4,40), distinctive flavor beans for the taste (4,28), and yellowish for the color (4,50). Keywords: β-carotene, nuts biscuits,red palm oil.